Efektivitas Antibakteri Ekstrak Daun Sirih Merah (Piper Crocatum) dan Sirih Hijau (Piper Betle L.) sebagai Bahan Alternatif Irigasi Saluran Akar (The Efectiveness of Red Piper Betle (Piper Crocatum) Leaf and Green Piper Betle (Piper Bettle L) Leaf Extract - Hafida Mariyatin; Ekiyantini Widyowati; Sri Lestari (Pustaka Kesehatan, 2014)
Background: Root canal irrigation is one, of important in endodonti treatment because if ignored can lead to failure. 3% Hydrogen peroxide (H2O2) is one of irrigation solution is often used. To reduce the effects of toxicity of root canal irrigation, it can be used for alternative materials canal irrigation are safe to use. One is piper betle plant. Based on previous research phytochemical test, the piper betle leaf has anti-bacterial effect. Purpose: This study aimed to determine the antibacterial effect, difference antibacterial effect and effectiveness of red piper betle leaf extract and green piper betle leaf compared with 3% H2O2 solution to Streptococcus viridans. Methods: This study is an experimental laboratory with research design post only control design. This study uses pitting. Each petridish divided into 6 holes, spilled A 3% H2O2, B sterile distilled water, C 50% red piper betle leaf extract, D 50% green piper betle leaf extract, E 100% leaf extract a red piper betle and F 100% green piper betle leaf extract. All incubated for 24 hours at 37 ° C and the inhibition zone diameter measured. Results: The results showed significant difference between the extracts of green and red piper betle. Statistical test with Mann Whitney test showed a significant difference between each group except 3% H2O2 and 50% green piper betle extract. Conclusions and Recommendations: Conclusions from this research are green piper betle leaf extract and red piper betle leaf extract can inhibit the growth of bacteria S. viridans. There were significant differences antibacterial effect between green piper betle leaf extract and red piper betle leaf extract with 3% H2O2 to S. Viridans. 100% Green piper betle leaf extract effective as an antibacterial against S. viridans. Need more research on the use of green piper betle leaf extract and red piper betle leaf extract as an alternative material of root canal irrigation. Keywords: antibacterial, red piper betle leaf, green piper betle leaf, H2O2 3%, root canal irrigation